2021
DOI: 10.1002/jbm.a.37273
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid adipose graft materials synthesized from chemically modified adipose extracellular matrix

Abstract: Decellularized extracellular matrix (ECM) from tissues is a promising biomaterial that can provide a complex 3D microenvironment capable of modulating cell response and tissue regeneration. In this study, we have integrated the decellularized thiolated adipose‐derived ECM, at different concentrations, with polyethylene glycol (PEG) using Michael addition between thiol and acrylate moieties. The potential for this material to support adipogenic differentiation of human adipose‐derived stem cells was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Further, the use of different digestion enzymes (e.g., α-amylase, collagenase, and pepsin) for the preparation of ECM hydrogels has a great impact on ECM bioactivity [ 82 ]. Chemical modification of dECM allows the integration of additional functionalities [ 176 ]. However, chemical modification of native dECM alters the integrity of the natural structure of the ECM.…”
Section: Influence Of Materials Properties On Adipose-derived Stem Ce...mentioning
confidence: 99%
“…Further, the use of different digestion enzymes (e.g., α-amylase, collagenase, and pepsin) for the preparation of ECM hydrogels has a great impact on ECM bioactivity [ 82 ]. Chemical modification of dECM allows the integration of additional functionalities [ 176 ]. However, chemical modification of native dECM alters the integrity of the natural structure of the ECM.…”
Section: Influence Of Materials Properties On Adipose-derived Stem Ce...mentioning
confidence: 99%
“…Organic solvent-mediated recombination has been used to prepare larger liposomes, but it often leads to denaturation of membrane proteins. 121 The adipose tissue was decellularized by repeated freeze−thaw and washed with isopropyl alcohol and detergent. The results showed that decellularized adipose tissue (DAT) can be used for wound healing and has a good effect on the repair of damaged soft tissue.…”
Section: The Preparation Of Decellularized Scaffoldsmentioning
confidence: 99%
“…Organic solvent-mediated recombination has been used to prepare larger liposomes, but it often leads to denaturation of membrane proteins . The adipose tissue was decellularized by repeated freeze–thaw and washed with isopropyl alcohol and detergent.…”
Section: The Preparation Of Decellularized Scaffoldsmentioning
confidence: 99%
“…Likewise, decellularized adipose tissue can be processed as a hydrogel sheet, with or without the incorporation of ASC; this has been used to successfully repair critical sized femoral bone defects in an immunocompetent murine model ( 9 ). Finally, it has been possible to further modify the properties of decellularized human adipose tissue matrices by chemical cross-linking to polyethyleneglycol via thiol/acrylate addition ( 10 ). When implanted subcutaneously in immunocompetent mice, these chemically modified decellularized adipose ECM constructs supported host cell infiltration and adipogenesis ( 10 ).…”
Section: The Past As Prologuementioning
confidence: 99%
“…Finally, it has been possible to further modify the properties of decellularized human adipose tissue matrices by chemical cross-linking to polyethyleneglycol via thiol/acrylate addition ( 10 ). When implanted subcutaneously in immunocompetent mice, these chemically modified decellularized adipose ECM constructs supported host cell infiltration and adipogenesis ( 10 ). Thus, there is ample evidence that decellularized adipose tissue is compatible with multiple formats (beads, foam, hydrogel, sheet) applicable to a myriad of clinical situations and conditions requiring a range of viscoelastic and tensile properties.…”
Section: The Past As Prologuementioning
confidence: 99%